2020
DOI: 10.3390/cancers12102850
|View full text |Cite
|
Sign up to set email alerts
|

Protein Disulphide Isomerase A1 Is Involved in the Regulation of Breast Cancer Cell Adhesion and Transmigration via Lung Microvascular Endothelial Cells

Abstract: Cancer cell cross-talk with the host endothelium plays a crucial role in metastasis, but the underlying mechanisms are still not fully understood. We studied the involvement of protein disulphide isomerase A1 (PDIA1) in human breast cancer cell (MCF-7 and MDA-MB-231) adhesion and transendothelial migration. For comparison, the role of PDIA1 in proliferation, migration, cell cycle and apoptosis was also assessed. Pharmacological inhibitor, bepristat 2a and PDIA1 silencing were used to inhibit PDIA1. Inhibition … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(33 citation statements)
references
References 68 publications
(100 reference statements)
1
31
0
Order By: Relevance
“…Because of the relative structural simplicity of DDA molecules, the mechanisms responsible for their target protein selectivity are of interest. PDIA1 has been investigated as a target for anticancer therapeutics, and PDIA1 inhibitors have established anticancer efficacy in preclinical models [46, 47]. AGR2 contributes to tumor progression by facilitating EGFR disulfide bonding and surface presentation [48].…”
Section: Discussionmentioning
confidence: 99%
“…Because of the relative structural simplicity of DDA molecules, the mechanisms responsible for their target protein selectivity are of interest. PDIA1 has been investigated as a target for anticancer therapeutics, and PDIA1 inhibitors have established anticancer efficacy in preclinical models [46, 47]. AGR2 contributes to tumor progression by facilitating EGFR disulfide bonding and surface presentation [48].…”
Section: Discussionmentioning
confidence: 99%
“…Extracellular PDIA1 enhances the adhesion and migration of breast cancer cells (MCF-7 and MDA-MB-231) by potentially activating β integrins through thiol switches [78]. Also, PDIA1 increases cancer cell adhesion to the endothelial monolayer and collagen type I rather than PDIA3 [78]. The function of AGR2 to promote metastasis is demonstrated in a rat model of overexpressing AGR2 by enhancing the adhesive property of the cells [92].…”
Section: Role Of Pdi In Breast Cancer Invasion and Metastasismentioning
confidence: 98%
“…However, it is also involved in lobuloalveolar development due to its ability to stimulate cell proliferation [77]. In the recent proteomic study reported by Stojak et al, PDIA1 is identified as a major isoform of PDIs present in human breast cancer cells (MDA-MB-231 and MCF-7) [78]. PDIA3 (ERp57) is found to be the second most abundant isoform in both cell lines.…”
Section: Overexpression Of Pdis and The Role Of Pdi In Breast Cancer Proliferationmentioning
confidence: 99%
See 2 more Smart Citations